PENGARUH JUMLAH ANGGOTA DAN MODAL SENDIRI TERHADAP SHU KUD DI KABUPATEN KAMPAR PROVINSI RIAU - Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstack: The cooperatives is a business entity that membered a people or legal entity with the bases its activities cooperative principles are based on the principle of kinship. SHU in cooperative is one factor to measure the success of the cooperative and also the welfare of the members. In this study aims to determine how much influence the number of members and own capital to the reception SHU KUD in Kampar regency. Locations in this study in KUD located in Kampar regency. Data obtained from the Department of Cooperatives and SMEs Kampar Regency the book year 2015. Techniques used random sampling and analyzing 38 KUD from 42 KUD active in Kampar regency which use formulas Slovin. The analysis used in this study using multiple linear regression. The results of analysis obtained variable results number of members does not affect the reception SHU KUD in Kampar, while its own capital and significant influence on the acceptance of SHU KUD in Kampar regency. From the results of research conducted recommended that cooperatives prioritize the quality of members not the quantity of the KUD members. Additionally KUD expected to priority and utilize its own capital owned by the cooperative and is also supported by external capital, which is expected to raise the reception to be obtained KUD SHU..Keywords: membership, own capital and net income ( SHU ).